International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC). A new collaborative global platform for global clinical trials targeting post-COVID19 patients. - Siqueira, Maria Isabel Cavalcante; Oliveira, Miriã Cândida; Moreira Lino, Maria Eduarda; Souza, Shayra Kellen Arantes; Augusto Moreira Silva, Guilherme; Silva Rosa Tomaz, Renata; de Morais Carrijo, Marilúcia; Lisboa Guedes, Thays; Nascimento Souza, Beatriz; Rosa Pereira Póvoa, Elisângela; Rodrigues Bernardes, Rubens; de Souza Galvão, Letícia; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: In response to the pandemic caused by COVID-19, World Health Organization (WHO), together with International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC), developed research protocols facilitating global collaboration and accelerating the understanding of the disease, to identify the potential symptoms and persistent sequelae in infected individuals, which can be used in different areas of health, that is, in primary care, at a hospital or outpatient level, both public and private. Objective: To describe the International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC) protocol as a new global collaborative platform for global clinical trials targeting post-COVID-19 patients. Methods: The standardized forms were developed from the COVID-19 Clinical Characterization Protocol (PCC) by the ISARIC/WHO working group composed of specialist researchers with experience in clinical research in different areas of medicine and public health, especially outbreaks and infectious diseases. Conclusion: It is expected that the creation of a database composed of different populations from all over the world will help in the characterization of risk factors, in the best form of clinical intervention and in the best prevention strategies for physical, neurological and psychosocial sequelae in the medium and long term in post-COVID-19 patients.